The specificity of conflict regulation of obligations arising from damage in private international law - Rudenko, Oksana (Chernivtsi, Ukraine : Yuriy Fedkovych Chernivtsi National University, 2022)
This article discusses the current problems of tort liabilities, taking into account current trends. Issues of tort/delict obligations are being studied in a comprehensive manner, taking into account the new legislation. In addition to the analysis of the current Ukrainian legislation, the legislation and doctrine of individual foreign states, as well as international treaties regulating non-contractual obligations in international law, are considered. The main goal of this study is to promote the strengthening of the legal grounds for the participation of Ukrainian individuals and legal entities in international relations and the harmonization and approximation of the ways of regulating non-contractual relations with the approaches adopted in international acts and in the legislation of most countries. The article reveals the specifics of non-contractual obligations and the peculiarities of their legal regulation with a special emphasis on tort/delict obligations. At the same time, attention is focused on the fact that in private international law the regulation of non-contractual (tort/delict) obligations provides for the simultaneous application of both ― international treaties and domestic law
Keywords: non-contractual obligations, private international law, lex loci delicti commissi